Analysis of Improving The Service Quality of Professional Cooperation in “XZY” Higher Education Based on Servqual, IPA and QFD - Muhammad Chusaeni; Bambang Syairuddin; I Ketut Gunarta (IPTEK Journal of Proceedings Series, 2020)
The Status of Legal Entity State Higher Education (PTN-BH) at the Institut Teknologi Sepuluh Nopember (ITS) gives full autonomy to the management of higher education. For ITS to be able to innovate in exploring revenue generators, Business Development and Management Agency (BPPU) was formed which functions to raise, manage funds, and develop business units. Professional cooperation as one of the most dominant ITS business unit in contributing ITS revenue. BPPU as the administrative center for professional cooperation services always try to provide excellent service, but there are still complaints about these services related to speed and accuracy. To analyze the level of quality of professional cooperation services, this research uses the Servqual, Importance-Performance Analysis (IPA) and Quality Function Deployment (QFD) methods. Servqual is used to analyze the gap between perception and customer expectations. The IPA method is used to measure the performance satisfaction expected and received by customers. And the QFD method is used to design priority strategies for improving service quality according to customer desires and technical capabilities by internal managers of professional cooperation. Servqual analysis results show the greatest gap between the perception variable and customer expectations, namely Em1 (understanding specific needs), Em2 (clarity of procedure), Rs2 (responsive service capability), and As3 (accuracy of cooperation services management). The results of the IPA analysis show that the variables in the quadrant A are the same as the results of Servqual Analysis which also have high priority to be handled, namely Em1, Em2, Rs2, and As3. In QFD analysis, these variables become customer requirements (whats) associated with technical responses (hows) obtained from internal BPPU management, and according to the house of quality diagram, the priority sequence of technical response is obtained, the priority of the technical response can be applied internally by BPPU so that FGDs are carried out, with the hope that a strategy for improving service quality can reduce complaints from professional cooperation customers.